Raio que o parta! assimilações do modernismo nos anos 50 e 60 do século XX e seu apagamento em Belém (PA) - COSTA, Laura Caroline de Carvalho da (Universidade Federal do Pará, 2015)
This work is result of a research developed by the Laboratório de Memória e Patrimônio Cultural (LAMEMO), from the Faculdade de Arquitetura e Urbanismo, Universidade Federal do Pará about the movement of non-classical architecture present in the State of Pará in the mid-twentieth century, who lent modernism elements to compose what is known today as "Raio que o parta" (RQP), contemplating his historiographical analysis from previous studies on the subject and the characterization of these types on the facades of three residential neighborhoods: Cidade Velha, Umarizal and Telégrafo. In all these three sites, one can see a considerable amount of copies, though each one presents a different context. In Cidade Velha, houses with these characteristics are common, which is a curious fact because it is an area where eclectic buildings toppled by organs of national heritage dominate the landscape. In Umarizal, although sensitive changes to their social and real state speculation over its history, it has great number of houses, but also high erasure rate. The number of copies and the popular characterization on the facades also justify the choice for the third cut, the neighborhood of the Telégrafo, where we find the most architectural renewal rate which has deactivated the RQP lines. Using tools such as street ethnography and semiotic analysis of facades, we identified 90 RQP homes in those neighborhoods, taking into account the relationship of the resident / owner with them, regarding to conditions for its removal / erasure, and aspects such as house modernization desires or judgment of changing value, identified by Riegl (2006).